1993
DOI: 10.1007/bf00021537
|View full text |Cite
|
Sign up to set email alerts
|

The origin of lysine-containing proteins in opaque-2 maize endosperm

Abstract: The reduction of zein synthesis in the maize (Zea mays L.) opaque-2 mutant is associated with an increased percentage of lysine in the endosperm protein. When expressed on an endosperm basis, we found that W64A opaque-2 contains 490 micrograms of lysine compared with 350 micrograms in W64A normal. SDS-PAGE analysis of endosperm proteins indicated that several non-zein proteins are more abundant in the mutant than in normal genotype. To determine the subcellular origin of these proteins, we separated an endospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
91
0
5

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 39 publications
7
91
0
5
Order By: Relevance
“…Because zeins do not contain lysine (16), all the protein-bound lysine comes from the nonzein fraction. Hence, the reduction in zein synthesis and the increased synthesis of nonzein proteins both contribute to the enhanced percentage of lysine in grain protein (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because zeins do not contain lysine (16), all the protein-bound lysine comes from the nonzein fraction. Hence, the reduction in zein synthesis and the increased synthesis of nonzein proteins both contribute to the enhanced percentage of lysine in grain protein (17).…”
mentioning
confidence: 99%
“…To investigate the basis for the pleiotropic increase in lysine-containing proteins in o2 maize, we identified genes whose expression is increased in this mutant (17). Elongation factor 1a (EF-la) was found to be one of several mRNAs whose level is significantly increased in the endosperm of W64Ao2 plants compared with its normal wild-type counterpart.…”
mentioning
confidence: 99%
“…eEF1A. For example, the levels of a-zeins, pyruvate orthophosphate dikinase, and acetolactate synthase were decreased in o2 mutants compared to wild type (Damerval and Le Guilloux, 1998;Hunter et al, 2002), while that of eEF1A was increased (Habben et al, 1993;Sun et al, 1997). For some enzymes involved in carbohydrate metabolism, such as glyceraldehyde-3-phosphate dehydrogenase and sorbitol dehydrogenase, earlier studies showed these proteins are increased in o2 mutants (Damerval and Le Guilloux, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Both of these effects contribute to the increased Lys content of the endosperm (Moro et al, 1996), but the molecular mechanisms responsible for the larger amount of Lys-rich proteins are unknown. Habben et al (1993) investigated the nature of the Lys-containing proteins that are increased in o2 and found that elongation factor 1A (eEF1A), a protein synthesis factor, is highly increased compared to wild type. Analysis of a large number of normal and o2 inbreds with extensive variability in Lys and eEF1A content showed this protein is highly correlated (r 5 0.9) with the protein-bound Lys of the endosperm (Habben et al, 1995;Moro et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation